(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2017)
Molecular imaging is the focus of an impressive scientific and technological development, especially in oncology. Positron Emission Tomography (PET) is a highly sensitive and accurate nuclear medicine imaging technology that provides a functional or metabolic assessment of various diseases conditions, along with accurate staging of illness extent. One major problem of this technique is the use of radioisotopes with short half-life, less than two hours, which in some cases makes the transport from the production facility to distant centers prohibitive. Based on its half-life (110 minutes) the fluorodeoxyglucose (FDG) is the most used radiopharmaceutical in PET scans. In Brazil, as has been occurring worldwide, the number of nuclear medicine centers is increasing. Currently there are 394 nuclear medicine services in Brazil; 123 of them performing PET scans in their routine. Until 2006 the production and selling of short half-life radioisotopes was monopoly of the Brazilian Nuclear Energy Commission. However, given the need for the use of short half-life radioisotopes in nuclear medicine centers very far from the government production facilities, in 2006 a Constitutional Amendment revoked the above mentioned state monopoly. This fact makes it possible the start of operation of private cyclotrons facilities in the country, for the production of various positron emitting radioisotopes. The aim of this study is to describe the current status of short half-life radioisotopes production in Brazil and discuss the expectations for the future.